The versatility of female images in Uzbek and Russian prose - Kalonova Nargiza Nurzhovna (Peerian Journals Publishing, 2024)
The article talks about female images in Russian and Uzbek literature of the 20th century, about heroines striving for self-realization and freedom from social restrictions, and talks about how times of change brought new ideas of equality and emancipation of women. And also about images, which reflect the complexity and diversity of women’s experience and the sociocultural factors that gave ideas about a woman.
Keywords: image of women; characters; society